ENGLISH-INDONESIAN TRANSLATION METHOD AND QUALITY OF INTERROGATIVE SENTENCE IN THE “HARVEST MOON: BACK TO NATURE” VIDEO GAME - Nurul Intan Sari; Muhammad Yudha Setyagalam (Universitas Musamus, 2020)
This research focuses on translation method and the impact of translation method toward translation quality of interrogative sentence in the Harvest Moon: Back to Nature video game. Descriptive qualitative method is applied in this research. The data are the interrogative sentences found in the Harvest Moon: Back to Nature video game and its translation. The source data are the video game entitled Harvest Moon: Back to Nature developed by Victor Interactive Software, published by Natsume and its translation by PALAPA. The results of the research show that there are 4 methods applied to the translation namely Communicative Translation, Literal Translation, Free Translation, and Word-for-Word Translation. From 71 data of interrogative sentence in Harvest Moon: Back to Nature video game, the dominant translation method used is Communicative Translation with 36 data (50.7%). For the translation quality. From 71 data, 53 data categorized as accurate translation (74.6%), 60 data categorized as acceptable translation (84.5%), and 68 data categorized as readable translation (95.8%). The translation methods applied in translating interrogative in the video game can produce good quality translation.